A comparative study of the morphology of the braincase and associated structures of early Therocephalia (Amniota: therapsida) - Firm, Lyndsey (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.